Age, growth and mortality in Buccinanops globulosus (Gastropoda: Nassariidae) from Golfo Nuevo (Argentina) - Avaca, Maria Soledad (2013)
Buccinanops globulosus is a commercially exploited gastropod common on coastal waters of the Southwestern Atlantic Ocean. We determined the age and estimated growth and mortality rates of B.globulosus in a population from Golfo Nuevo (Patagonia, Argentina). Age was determined by counting opercular rings and growth was described by the von Ber length-at-age. Mortality rate (Z) was estimated by the linearized catch curve method. The maximum age was determined at eight years. Growth parameters estimated for the whole population were TSL∞ = 37.87 mm, k = 0.33 y -1 and t0 = - 0.65 y. Likelihood ratio tests indicated significant differences in asymptotic length and fitted growth models between sexes. Annual mortality rate (the first reported for the species) was estimated to be 0.64 y -1 (0.52 ? 0.76). Information on growth parameters of B. globulosus showed that TSL∞ and the index of overall growth performance (ɸ) of the population here studied were intermediate as compared to those previously studied populations, thus indicating sitespecific growth differences. Taking into account that the most common management strategy in gastropod fisheries is the use of a minimum size limit (MSL), we suggest that fisheries measures such as MSL for this species should be established only for small geographical scales.